Catering for adult learners through the transformation of higher education. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2009)
A ten year research (1996-2006) conducted in the United States on American adults returning to school identifies several reasons, the primary being to equip themselves with knowledge and skills needed for their careers and better prospects (Aslanian, 2007).